Students’ Perception on Tandem: Language Exchange Application As a Learning Media to Improve Speaking Skills - Nurul Mifta Lubis; Emeliya Sukma Dara Damanik; Maryati Salmiah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The research that has been carried out is entitled